Modern trends in elite high jumpers' running start improvement domain - Shustova, E. V.; Kulishenko, I. V.; Shustov, A. A. (Journal of Athletic Training, 2018)
The study analyzes the ways to improve the high jump movement sequence in the approach phase, with the video captures of the approach sequences of 34 elite high-jumpers in the XIV World Track and Field Championship in Beijing being subject to analysis. A special priority was given to a few approach specifics including the startup and middle (straight run) phase versions/ styles versus the personal best (PB) results of the jumpers. The individual technical performance specifics of the approach phase by A. Shustov, European Champion and Honorary Master of Sport were rated by 13 rating parameters tracked using the video replay processing and analyzing Dartfish software. Based on the study findings, we recommend that the athletes with the high-speed approach should accelerate in the middle (straight run) approach phase making a special emphasis on the run pace and rhythm to facilitate the speed control at the final stage of the approach including the pace control aggression. Such an approach control pattern is designed to naturally lift the body mass center (BMC) and thereby facilitate the postural control in the take-off phase. The study data were applied to offer a few ways to improve the approach phase, including its customization to the individual motor asymmetry profiles when calculating optimal strides.